Implications of Russia's Aggression Against Ukraine for its Membership at the UN Human Rights Council - Vanesha Salsabila Keisya (JUSTICES: Journal of Law, 2025)
Russia has engaged in military operations leading to aggression since 2014 on the Crimean peninsula, culminating in Russia opposing Ukraine's desire to join the North Treaty Organization (NATO) in 2022. Russia is a member state in the UN Human Rights Council since 2020, as a result of violating human rights has resulted in Russia's membership status in the UN Human Rights Council being suspended. In accordance with the provisions of the establishment of the UN Human Rights Council through the UN General Assembly Resolution, namely MU-UN Resolution 60/251 entitled "UN General Assembly Resolution: Human Rights Council". The problems in this study, namely: How is Russian aggression against Ukraine based on international law. What are the implications of Russia's aggression on its membership status in the UN Human Rights Council. The research method is based on descriptive normative juridical research and the data is analyzed in qualitative terms. The results of the research are drawn conclusions: Russian aggression against Ukraine based on international law has violated several provisions of international law, namely the UN Charter in Article 62 paragraph (2), the 1998 Rome Statute in Article 5 and Article 8 bis, the 1949 Geneva III Convention especially Chapter II Articles 13, 14, 15, the Geneva IV Convention, and several UN General Assembly Resolutions. The implications of Russia's aggression against Ukraine caused Russia's membership status in the UN Human Rights Council to be suspended based on UN Resolution 60/251 of 2006, especially in paragraph 8.